2021
DOI: 10.3390/foods10102370
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Biogenic Amines in 35 Korean Cottage Industry Traditional Gochujang (Fermented Red Pepper Paste) Products

Abstract: Traditional gochujang is well known for its distinguished flavor and taste. However, the safety of cottage industry gochujang products is uncertain, particularly, in terms of biogenic amine (BA) content which is not yet documented. The present study aimed to determine the level of BAs present in 35 traditional gochujang products nationwide. All gochujang products had considerable amounts of total BAs ranging from 52.95 mg/kg to 176.24 mg/kg. Individually, histamine and tyramine were either not detected or dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…In the present study, all the tested gochujang products were prepared using salt supplements between 5% and 12%, which further impacted the salinity of the final product [1]. During the gochujang fermentation process, salinity increase was also detected by Beak et al [27], whereas a decrease in salinity was reported by Ryu et al [24].…”
Section: Salinitysupporting
confidence: 46%
See 4 more Smart Citations
“…In the present study, all the tested gochujang products were prepared using salt supplements between 5% and 12%, which further impacted the salinity of the final product [1]. During the gochujang fermentation process, salinity increase was also detected by Beak et al [27], whereas a decrease in salinity was reported by Ryu et al [24].…”
Section: Salinitysupporting
confidence: 46%
“…One-way analysis of variance in a completely randomized design and Duncan's multiple range comparison tests were used to explore the significant differences between the samples with a 95% confidence interval at p < 0.05. The multivariate exploratory techniques of principal component analysis (PCA) were conducted to categorize the gochujang samples based on their pH, lightness, redness, yellowness, amino nitrogen content, aerobic mesophilic bacteria count, yeast/mold count, and major volatile compound profile using the XLSTAT package on Microsoft Office Excel 2016 version [1].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations